The factor intensity of accession and EU15 countries' comparative advantage in the internal market - Ville Kaitila (The Research Institute of the Finnish Economy (ETLA), 2004)
Economic relations between the European Union and the accession countries of Central and Eastern Europe (CEE) were liberalised by Europe Agreements after the early 1990s. Free trade and investment have the potential of changing the structure of countries' trade although with some restrictions set by, inter alia, the quantity and quality of the available factors of production. The accession countries have lower labour costs coupled with a relatively well-educated labour force. We analyse the factor intensity (skilled/unskilled labour and capital) of the accession countries' comparative advantage in the internal market in 1993-2002. Most accession countries' comparative advantage remains less skillintensive than that of the EU15 countries. A movement towards a more skillintensive comparative advantage is shown to have been positively correlated with higher growth rates in the EU15 and the CEE countries. – – Taloussuhteet Euroopan unionin sekä Keski- ja Itä-Euroopan (KIE) EU-hakijamaiden välillä liberalisoitiin Eurooppa-sopimuksilla 1990-luvun alun jälkeen. Vapaa kauppa ja investoinnit saattavat muuttaa maiden välisen ulkomaankaupan rakennetta, joskin rajoitteita tuovat muun muassa tarjolla olevien tuotannontekijöiden määrä ja laatu. KIE-maissa on EU15-maita alemmat työvoimakustannukset sekä suhteellisen koulutettu työvoima. Tässä tutkimuksessa analysoidaan KIE-maiden suhteellisen edun panosintensiivisyyttä (koulutettu/kouluttamaton työvoima sekä pääoma) niiden viennissä EU15-alueelle vuosina 1993-2002. Useimpien KIE-maiden suhteellinen etu on painottunut alemman osaamisintensiivisyyden tuotteisiin kuin EU15-maiden vastaava suhteellinen etu. Siirtymä kohti osaamisintensiivisempiä tuotteita on korreloinut positiivisesti nopeamman talouskasvun kanssa EU15- ja KIE-maissa. – EU ; itälaajeneminen ; suhteellinen etu ; panosintensiivisyys
Keywords: 330; EU; eastern enlargement; comparative advantage; factor intensity; EU-Erweiterung; Faktorintensität; EU-Binnenmarkt; Komparativer Kostenvorteil